Phylogenetic relationships and characterization of the complete mitochondrial genome of Eriobotrya japonica in southeast of China - Yang, Jun (Mitochondrial DNA B Resour, 2019)
Eriobotrya japonica is an evergreen fruit tree originating in southeastern China. Its fruit is juicy with a pleasant taste and considerable medical value. However, there is no complete mitochondrial (cmt) genome resource for this species. This is the first report of the cmt genome of Eriobotrya japonica from southeastern China. The whole cmt genome was 434,980 bp in size with 37.80% GC content. The cmt genome of Eriobotrya japonica contains 41 protein-coding genes, 22 tRNA genes, and 3 rRNA genes. A phylogenetic maximum-likelihood (ML) tree was constructed based on 22 mitochondrial genomes from plant species. Eriobotrya japonica grouped closely with other Rosaceae species, which provides strong support for the traditional classification.